PENGARUH DRAMA KOREA TERHADAP LITERASI DIGITAL DAN KEMANUSIAAN - Lintang Ratu Wastika; Ranu Iskandar (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Korean drama, or K-Drama, has become a widespread popular cultural phenomenon in many countries, including Indonesia, and has a significant influence on media consumption patterns and digital literacy among young people. This study uses a descriptive-qualitative approach based on a literature review to further explore the influence of Korean drama on digital literacy and humanitarian values among the younger generation. The study focuses on how Korean drama affects these aspects. The findings indicate that watching Korean dramas encourages young people to actively use digital media and technology to search for, understand, and produce digital information. This indirectly enhances their digital literacy skills, including the ability to think critically, evaluate information sources, and communicate digitally. Korean dramas also teach social and moral values such as tolerance, empathy, and social care. These values can strengthen humanitarian values in society if they are well received and practiced. However, the study also shows that excessive consumption has the potential to disrupt productivity, reduce direct social interaction, and increase the likelihood of social isolation, all of which can damage the quality of humanity. This study affirms that Korean drama has a dual potential: as a form of entertainment and an effective educational tool to shape a digitally literate and highly humane younger generation. The successful utilization of Korean drama heavily depends on wise media consumption management as well as support from education and families in creating a balance between the digital world and the real world. The results provide recommendations for educators, parents, and policymakers to guide the healthy and productive use of digital media. This will enable the maximization of digital literacy and humanitarian values in the era of globalization.